(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyzes the role of Expected Credit Loss (ECL) mechanisms under IFRS 9 in proactive credit risk management. The results show that the ECL approach is an important tool for early identification of nonperforming loans (NPLs) and strengthening the quality of bank assets.